A tomato B-box protein regulates plant development and fruit quality through the interaction with PIF4, HY5, and RIN transcription factors - Shiose, Lumi (2024)
During the last decade, the knowledge about BBX proteins has abruptly increased. Nevertheless, the mode of action of these factors has been mostly unveiled in Arabidopsis thaliana and investigated during photomorphogenesis and flowering processes. Whilst, beyond this model species, genome-wide studies identified BBX gene family in several ornamental, industry and food crops; the reports regarding the role of these genes as regulators of agronomically important traits are scarce. Here, by phenotyping a knockout mutant, we performed a comprehensive functional characterization of Solyc12g089240 locus, hereafter called SlBBX20. The data revealed this protein as a positive regulator of photomorphogenesis, shade avoidance, vegetative growth and ripening-related processes that, ultimately, contribute to determining yield, fruit quality and fungal tolerance. Furthermore, we found that SlBBX20 function is mediated by its heterodimerization with master transcriptional factors of light and ripening signaling i.e. ELONGATED HYPOCOTYL 5 (SlHY5), PHYTOCHROME INTERACTING FACTOR 4 (SlPIF4) and RIPENING INHIBITOR (SlRIN). This work clearly demonstrates that BBX proteins are multilayer regulators of plant physiology, not only because they affect multiple processes along plant development but also regulate other genes at the transcriptional and post-translational level.